PERFORMANCE OF GROUNDNUT (Arachis hypogaea L.) VARIETIES AS INFLUENCED BY PHOSPHORUS AND MULCHING IN THE NIGERIA SAVANNA - Shamsuddeen, Ladan; Bashir, Aminu Abdullahi (FUDMA JOURNAL OF SCIENCES, 2025)
The study on groundnut (Arachis hypogaea L.) performance under different rates of phosphorus and mulching in the Nigeria savannas addresses challenges of low soil fertility and harsh climatic conditions. Groundnut, an important crop in Nigeria, is limited by phosphorus deficiency and soil moisture stress in the savannas. Phosphorus is vital for root development, flowering, and seed production but is often deficient in the region’s alkaline soils. Mulching helps conserve moisture, reduce erosion, and improve fertility by adding organic matter. Identifying optimal combinations of phosphorus and mulching can enhance groundnut yield and sustainability. Field trials were conducted at the Irrigation Research Farms of the Institute for Agricultural Research, Samaru and Kadawa in dry season of 2024 to evaluate two varieties of groundnut (SAMNUT-24 and SAMNUT-25), three phosphorus rates 0, 30 and 60 kgP205ha-1), and three mulch materials (no mulch, polythene sheet and rice straw). Treatments were laid out in a randomized complete block design with three replications. Results showed SAMNUT-24 excelled in branches, canopy spread and shoots dry weight, while SAMNUT-25 produced higher pod yield and harvest index. Applying 60 kgP205 ha-1 improved leaves, pod yield and harvest index, while polythene sheets enhanced leaf number and canopy spread. Both varieties performed well under irrigation. SAMNUT-24 and SAMNUT-25 with 60 kgP2O5ha-1 and rice straw mulch is recommended for farmers. Further research is needed to explore phosphorus rates with new/improved varieties.